Character association among physiological and yield attributes in kabuli chickpea (Cicer arietinum L.) - N. Jagadish and V. Jayalakshmi (Electronic Journal of Plant Breeding, 2015)
Character association studies among physiological and yield attributes in 21 kabuli chickpea genotypes revealed that shoot biomass per plant and number of branches per plant are most important traits contributing directly to the seed yield. Besides traits like days to first flowering, days to 50 per cent flowering, number of branches per plant, SCMR, SLA also influenced seed yield per plant indirectly through shoot biomass per plant. Trait 100- seed weight though exhibited negative correlation with seed yield per plant, its indirect influence via other traits is positive indicating that the association between number of pods per plant, 100 seed weight and shoot biomass per plant should be considered carefully while selecting high yielding genotypes. Physiological traits like SLA, SCMR and RWC which are related to photosynthesis efficiency and water use efficiency exerted indirect and positive effects via other traits. Thus integration of these physiological traits in breeding programmes will greatly enhance the progress expected, especially in breeding for drought prone environments.